An accurate ab initio potential energy curve and the vibrational bound states of X 2 Σu + state of H 2 - - Sathyamurthy, N. (Elsevier, 2012)
Potential energy curve for the X2Σu+ state of H2- has been computed at the full CI/cc-pVXZ (X = D - Q) level. An analytic function is fitted to the resulting potential energy curve and is then used to calculate the vibrational bound states of H2- and compared with those for H 2.
Only IISERM authors are available in the record.
Keywords: Anions; Electron scattering; H 2 -; Potential energy curve